High‐Performance Plasmonic Sensors Based on Two‐Dimensional Ag Nanowell Crystals. Issue 8 (24th June 2014) - Ye, Shunsheng; Zhang, Xuemin; Chang, Lingxia; Wang, Tieqiang; Li, Zibo; Zhang, Junhu; Yang, Bai
<x xml:space="preserve">Abstract</x> A high‐performance plasmonic biosensor based on two‐dimensional (2D) Ag nanowell crystals is rationally designed and fabricated by colloidal lithography. The crystals act as 2D metallic gratings that directly couple incident photons to surface plasmon polaritons (SPPs). The nanowell sizes are properly tuned to enable coupling between the SPPs and Raleigh anomalies, which proves to greatly contribute to sharp reflectance dips. Other geometric parameters including the nanowell depth and the lattice constant are respectively adjusted to optimize the lineshape and sensitivity. These inferences and experimental results are verified by finite‐difference time‐domain (FDTD) calculations. In this study, the fabricated crystal with 670 nm lattice constant, 483 nm nanowell size, and 40 nm nanowell depth possesses the highest refractive index sensitivity (RIS) (623.7 nm RIU−1), the maximum figure of merit (FOM) (55.2 RIU−1), and a very high value of full height/full width at half‐maximum (FH/FWHM) (28.3 ×10−3 nm−1). As a proof‐of‐concept, we adopt the well‐studied antigen‐antibody couple as a model system to illustrate the potential of the nanowell crystal in a quantitative analytical bioassay. The excellent sensing performance, together with the compact structure and the simple read‐out apparatus, suggest that the 2D Ag nanowell crystal is an excellent candidate for a label‐free biosensing platform.